Peran Guru dalam Pembentukan Akhlakul Mahmudah di Madrasah Ibtidaiyah - Musyaffa, A.A; Windari; Wahyuningtyas, Ika Panggih (IBTIDA', 2024)
In overcoming the diverse character of students, it is necessary that the role of teachers in the formation of akhlakul mahmudah is an important part of the school environment of Madrasah Ibtidaiyah Al-Mukhlisin. This study uses a descriptive qualitative method. The instruments of this research use interviews, observations, and documentation of data sources used are school principals, grade IV homeroom teachers, moral faith teachers, and grade IV students. This study uses the following data analysis methods: data collection, data reduction, data presentation, and summary of research results. The results of the study show that teachers have a significant influence on the moral development of their students through guidance and direction, which they include various religious activities in the school curriculum. In addition to the diverse traits and characteristics of students, it requires an individual approach to each student, such as internal and environmental factors also provide an influence that hinders the formation of simple moral values in students. Teachers need to implement strategies to instill akhlakul mahmudah in students who are positive role models for students to cultivate habits, provide guidance and direction to students, and show a firm attitude towards students.